ASSESSMENT OF THREE-DIMENSIONAL BAROCLINIC CIRCULATION MODEL FOR THE MUSI COASTAL AREA - Septy Heltria; Amir Yarkhasy Yuliardi; Gentio Harsono; Marita Ika Joesidawati (Marine Geological Institute of Indonesia, 2023)
The hydrodynamics of the Musi estuary ecosystem is influenced by the flow of water discharge from the river, tidal circulation within the estuary, and complex bathymetry. Numerical modeling is one of the best ways to explain the characteristics and processes occurring in the estuary. However, the obtained model requires validation to ensure its accuracy despite the complexity added by variability in tidal and bathymetric conditions, making the validation process more challenging. This difficulty can be overcome by using high-resolution data, which provides a refined understanding of the river-to-sea estuary flow and its variability. The validation process involves the use of conductivity-temperature-depth (CTD) instruments and mooring tidal stations. The validated model is considered capable of accurately simulating tidal propagation as it represents the temperature-salinity-density properties within the estuarine environment. The development of this model demonstrates the effective implementation of these parameters within the Musi estuary ecosystem domain. The 3D model simulation is used to consider the vertical discretization in the river-estuary-sea channel, which enhances the representation of temperature-salinity-density in the water column. The obtained results suggest that the 3D-MIKE modeling is well-suited for operational purposes, including the prediction of hydrodynamics and the management of estuarine areas, specifically in the Musi estuary ecosystem.